Warfarin for the prevention of systemic embolism in patients with non-valvular atrial fibrillation: a meta-analysis. Issue 12 (20th January 2008) - Andersen, L V; Vestergaard, P; Deichgraeber, P; Lindholt, J S; Mortensen, L S; Frost, L
Abstract : Background: Warfarin for stroke prevention in patients with atrial fibrillation (AF) is well documented. However, it has not been examined in the prevention of systemic embolism. Objectives: To evaluate the efficacy of warfarin in preventing systemic embolism (embolism to limbs or viscera) in patients with AF. Methods and results: A combined Medline, Embase, Cochrane Library and SveMed+ search were made. Fifteen studies were included. Warfarin was better than antiplatelet agents for preventing systemic embolism with a 50% reduction of risk (odds ratio (OR) = 0.50, 95% CI 0.33 to 0.75) without increasing the risk of major bleeding (OR = 1.07; 95% CI 0.85 to 1.34). Warfarin compared with placebo resulted in a risk reduction of 71% (OR = 0.29; 95% CI 0.08 to 1.07) with higher risk of major bleeding with warfarin (OR = 3.01; 95% CI 1.31 to 6.92). Results of a comparison of warfarin with low-dose warfarin (OR = 1.52; 95% CI 0.40 to 5.81) or low-dose warfarin with aspirin (OR = 1.00; 95% CI 0.17 to 5.81) were inconclusive. Conclusions: Warfarin not only reduces the risk of stroke but is also better than placebo and antiplatelet agents in prevention of systemic embolism in patients with non-valvular AF. Warfarin increases the risk of major bleeding compared with placebo but not compared with antiplatelet agents.